STUDI AWAL NANOREAKTOR KIRAL BERBASIS KUKURBITURIL - Ambarwati, Masyitha
Enzymes are well known molecules which catalyzes reactions with extremely high catalytic efficiency and specificity under mild conditions. Reaction pocket of enzymes are capable of enhancing catalytic efficiency and stereocontrol during chemical transformation by governing substrates in preferential orientation and conformation. Inspired by nature, supramolecular bearing hydrophobic cavity, which is able to accommodate the interaction between reactant and substrate through Host-Guest interaction, are a good candidate for the development of enzyme-mimetics. Cucurbituril (CBs) are an example of supramolecular that has been proven to promote both photochemical and thermochemical reactions as well as improved stereo-/chemo-selectivities. However, due to the intrinsically non-chiral property of CBs as well as the nontrivial synthetic efforts in constructing the chiral supramolecular assembles, utilizing CBs in symmetric catalysis remains a challenge. To address these challenges, we design a cucurbituril-based chiral nanoreactor. As a model to study the enzyme mimetic chiral nano-reactor, the enantioselectivity and the reactivity of chiral nano-reactor, which is sustained by inclusion of amino acid-Cu2+ complex inside CBs cavity, were performed in Lewis acid catalyzed asymmetric Diels-Alder (D-A) reaction. In the present study, the Lewis-acid catalyzed D-A reaction between azachalcone and cyclopentadiene in aqueous medium were chosen as a model system. The racemic products were obtained with CBs as the only ligand. Enantioselectivity achieved upon addition amino acids as ligand. This result indicating the enanoselectivities can only be induced by chiral amino acids. The optimum enantioselectivity of product of the D-A reaction was achieved at pH 7.4, confirmed by HPLC using chiral stationary phases, UV-Vis spectra and fluorescence. Enantioselectivity D-A reaction product was analyzed using HPLC at the retention time ±14 and ±17 minute, the ee value were calculated from peak areas. From this work, only with a catalytic amount of the reactor (0.5% mol), we enhanced stereoselectivity and enantioselectivity (by 40%). To gain more insight in interaction between chiral nanoreactor and substrate fluorescence and UV-vis spectroscopy analysis were performed. From fluorescence measurements, where not only fluorescence quenching but also distinct blue shift (? 20 nm) was observed upon the addition of CB[8]. This result indicates the inclusion of indole ring of Tryptophan. Moreover, shape changes in UV-Vis absorption of tryptophan indicated that there were closer interaction between amino acids and substrate inside CB[8] cavity. Enantioselectivity increase is most probably because of the closer interaction between the aromatic side chain of amino acid and substrate due to the presence of CB[8]. The catalytic activity of the D-A reaction was measured from the initial decrease in absorption of azachalcone. In the presence of CBs, the rate acceleration was 10 fold higher due to an increased affinity of dienophile toward the curcubiturils bound copper complex was observed. This is the first time demonstration of that CBs play an active role in affecting enantioselectivity. Moreover, during product formation dramatic rate acceleration of the reaction was also achieved due to the presence of CB[8]. As the outlook, the concept of the current design is the dramatically decreased usage of rather expensive chiral resources. As such, we believe that this work will open the door for more types of asymmetric reactions based on other non-chiral artificial cavities.